2012
DOI: 10.1111/j.1537-2995.2012.03581.x
|View full text |Cite
|
Sign up to set email alerts
|

The United States Trypanosoma cruzi Infection Study: evidence for vector‐borne transmission of the parasite that causes Chagas disease among United States blood donors

Abstract: This report adds 16 cases, including one from the Mississippi investigation, of chronic T. cruzi infection presumably acquired via vector-borne transmission in the United States to the previously reported seven cases. The estimated prevalence of autochthonous infections based on this study is 1 in 354,000 donors. Determining US foci of vector-borne transmission is needed to better assess risk for infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 22 publications
1
133
0
2
Order By: Relevance
“…The US CDC recently reported rare cases of domestically acquired infection from a large nationwide follow-up study of infected blood donors. 12 In contrast, our pilot study of 17 RIPA-positive blood donors in the Houston area found 35% (6 of 17) with evidence of locally acquired infection.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The US CDC recently reported rare cases of domestically acquired infection from a large nationwide follow-up study of infected blood donors. 12 In contrast, our pilot study of 17 RIPA-positive blood donors in the Houston area found 35% (6 of 17) with evidence of locally acquired infection.…”
Section: Discussionmentioning
confidence: 62%
“…These two exposure activities have also been previously described in United States domestically acquired case reports. 12 Inadequate temporary lodging and/or increased exposure to the vector during these activities may be important contributing factors for transmission associated with these outdoor activities. 19 Exposure to infectious blood while skinning a dead animal without gloves is another possible important transmission route.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations